KINERJA DINAS PERTANIAN DALAM PENYALURAN BANTUAN BIBIT KELAPA SAWIT DI KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Nadia Turahma; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The distribution of palm oil seedlings by the Agriculture Service is assistance from the Kuantan Singingi Regent. In the implementation there were problems such as the Decree of the Agriculture Office and the Kuantan Singingi Regent which contained unclear and detailed information, the placement of staff not in the field, the transparency of information on the existence of seed assistance programs by the Agriculture Service, and the coordination and communication of the Agriculture Service with farmer groups that had not run optimally . This study aims to find out and analyze the forms of implementation performance and the factors that hinder the distribution program of palm oil seedlings by the Kuantan Singingi District Agriculture Service. This study uses a qualitative method with a phenomenological approach. Data collection techniques through observation, interviews, and documentation. This method uses the theory of organizational performance from Dwiyanto with performance indicators namely productivity, service quality, responsiveness, responsibility and accountability. From the results of this study it was found that the implementation of the distribution of palm oil seedlings was not optimal because there were several factors that inhibited the limited available and insufficient budget to reach the budget for purchasing superior oil palm seeds that had to be channeled, inadequate availability of human resources and the ability to understand and place the position of employees in accordance with their fields in their respective duties and functions as well as outside constraints when the Kuantan Singingi District Agricultural Service conducts the distribution of palm oil seedlings. External factors here are contractors providing palm oil seeds. Keywords: Assistance, Palm Oil Seeds, Performance, Implementation